2016
DOI: 10.4314/jae.v20i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Use of internet for innovation management by extension agents in Oyo State

Abstract: Abstracts This study examined extension agents' perception of the use of the Internet for sourcing and disseminating agricultural innovation in (2008) opined that frontline extension workers, who are the direct link between farmers and other stakeholders in the agricultural knowledge transfer and information management system should be well positioned to make use of information communication technologies (ICT) to access expert knowledge and other types of information that could be beneficial to farmers. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…The mean age is 43.1250 years which implies that most of the extension agents in the study area are still productive but are gradually getting old, outliving their productive age. This agrees with the findings of Aromolaran et al, (2016), that majority of extension agents in Oyo State were above 40 years of age. It also shows that 70.0% of the respondents were male while 30.0% were female.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mean age is 43.1250 years which implies that most of the extension agents in the study area are still productive but are gradually getting old, outliving their productive age. This agrees with the findings of Aromolaran et al, (2016), that majority of extension agents in Oyo State were above 40 years of age. It also shows that 70.0% of the respondents were male while 30.0% were female.…”
Section: Resultssupporting
confidence: 93%
“…The important task of extension is the exchange and sharing of information, knowledge and skills. New media such as different internet platforms which include agricultural websites, WhatsApp and Facebook are fast means of disseminating innovation to farmers and obtaining quick feedbacks, but extension services still adhere to old extension methods of contacts which have been individual and group methods that result in a delay in feedback (Aromolaran et al, 2016). The use of internet-based mobile apps enhances researchers and extension workers job commitments also saving time, but fluctuations of internet connectivity and epileptic power supply were factors influencing the use of internet-based mobile apps (Oose, Fapojuwo and Agbabiaka, 2021).…”
mentioning
confidence: 99%
“…However, in Nigeria, there are number of challenges that could hinder the successful implementation of agricultural policies at the state level, most of which are related to the capacity, competency, and performance of state ADP personnel, given their major role in the implementation of agricultural extension policies at the state and farmer levels (Issa 2013;Umeh et al 2015). Additionally, several studies (Ekerete and Ekanem 2015;Apantaku et al 2016;Cynthia and Nwabugwu 2016;Aromolaran et al 2016) have shown that many public extension agents are less information and communication technology (ICT) compliant, and the ICT utilization rate is low. Many agents are less motivated to seek knowledge on or familiarize themselves with trending issues within their core areas of expertise.…”
Section: Weak Capacity and Technical Know-how Of Extension Personnelmentioning
confidence: 99%
“…The study concluded that a considerable number of the households were in the very low food security category. Also, Aromolaran et al, (2017), in a survey among rural communities in Nigeria observed that the Majority 86.7% of the farming households in the survey were food insecure, as against few (13.3%) of the respondents that were categorized as a food secured. These studies corroborate the current findings.…”
Section: Article | Open Accessmentioning
confidence: 96%